Highly fluorescent nitrogen and boron doped carbon quantum dots for selective and sensitive detection of Fe3+. Issue 23 (21st May 2021) - Zhang, Yunhao; Qin, Hongxin; Huang, Yuting; Zhang, Feng; Liu, Hairong; Liu, Hongbo; Wang, Zi Jun; Li, Run
Abstract : Nitrogen and boron co-doped carbon dots with a core–shell structure for selective and sensitive Fe 3+ detection. Abstract : Due to the essential role of Fe 3+ in physiological and pathological processes, the detection of Fe 3+ has drawn increasing attention in the field of disease diagnosis and environmental protection. However, most existing methods require either cumbersome sample pretreatment or sophisticated and expensive test equipment. Recently, carbon quantum dots have found a wide range of applications such as nanoprobes for Fe 3+ determination, albeit with limited sensitivity and selectivity. Herein, we report core–shell carbon quantum dots B1 N2 CQDs via a two-step hydrothermal approach using citric acid, boric acid and ethylenediamine as precursors. The obtained B1 N2 CQDs exhibit excellent water solubility and remarkable stability as well as a high fluorescence quantum yield of 15.4%. In addition, the fluorescence of B1 N2 CQDs is quenched exclusively by Fe 3+ with minimal interference from other metal ions. A linear relationship with R 2 = 0.998 was observed between the fluorescence quenching capacity and the Fe 3+ concentration in the range of 2–160 μM, with the limit of detection calculated to be 80 nM. Finally, the as-prepared B1 N2 CQDs were successfully applied as a highly efficient fluorescent probe for Fe 3+ detection in river water samples and intracellular Fe 3+ imaging in biological systems.